Eating disorders in sport: Review of prevalence, risk factors, and studies of eating disorders in highly competing athletes - Ismailova, Dilyara; Gazdowska, Zuzanna (Journal of Education, Health and Sport, 2016)
Ismailova Dilyara, Gazdowska Zuzanna. Eating disorders in sport: Review of prevalence, risk factors, and studies of eating disorders in highly competing athletes. Journal of Education, Health and Sport. 2016;6(6):351-358. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55703 http://ojs.ukw.edu.pl/index.php/johs/article/view/3588 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 10.06.2016. Eating disorders in sport: Review of prevalence, risk factors, and studies of eating disorders in highly competing athletes Dilyara Ismailova University of Social Sciences and Humanities, Warsaw, Poland Zuzanna Gazdowska University of Social Sciences and Humanities, Warsaw, Poland Dilyara Ismailova University of Social Sciences and Humanities, Warsaw, Poland mgr Zuzanna Gazdowska University of Social Sciences and Humanities, Warsaw, Poland; zgazdowska@swps.edu.pl Abstract In today’s society, where thinness is idealized and correlates with good personal characteristics, people resort to different actions in order to comply with social norms. Athletes do not differ; they face the same issue of body image and weight concerns as the rest of the society. In addition to general factors of eating disorders, they have an extra pressure from their sport environment to maintain certain body weight and body measurements. This type of pressure puts them in the high-risk zone for developing clinical eating disorders (Brownell, 1991; Byrne & McLean, 2002; Rodin & Larson, 1992; Smolak, Murnen, & Ruble, 2000). Numerous studies investigated this problem related to variety of risk factors (Krentz & Warschburger, 2011; Picard, 1999; Sundgot-Borgen, 1994). This paper is focused on reviewing the available and newest literature on prevalence, risk factors, and consequences of eating disorders in sport, specifically among elite athletes. Key words: eating disorders, eating disorders in sport, sport psychology.